The transcriptional program underlying the physiology of clostridial sporulation - Jones, Shawn W (BioMed Central, 2008)
BACKGROUND: Clostridia are ancient soil organisms of major importance to human and animal health and physiology, cellulose degradation, and the production of biofuels from renewable resources. Elucidation of their sporulation program is critical for understanding important clostridial programs pertaining to their physiology and their industrial or environmental applications. RESULTS: Using a sensitive DNA-microarray platform and 25 sampling timepoints, we reveal the genome-scale transcriptional basis of the Clostridium acetobutylicum sporulation program carried deep into stationary phase. A significant fraction of the genes displayed temporal expression in six distinct clusters of expression, which were analyzed with assistance from ontological classifications in order to illuminate all known physiological observations and differentiation stages of this industrial organism. The dynamic orchestration of all known sporulation sigma factors was investigated, whereby in addition to their transcriptional profiles, both in terms of intensity and differential expression, their activity was assessed by the average transcriptional patterns of putative canonical genes of their regulon. All sigma factors of unknown function were investigated by combining transcriptional data with predicted promoter binding motifs and antisense-RNA downregulation to provide a preliminary assessment of their roles in sporulation. Downregulation of two of these sigma factors, CAC1766 and CAP0167, affected the developmental process of sporulation and are apparently novel sporulation-related sigma factors. CONCLUSION: This is the first detailed roadmap of clostridial sporulation, the most detailed transcriptional study ever reported for a strict anaerobe and endospore former, and the first reported holistic effort to illuminate cellular physiology and differentiation of a lesser known organism.